Cocoa Tree, Trinidad - (:unkn) unknown (Davidson and Todd, Ltd., 2010)
A picture of a cocoa tree full of its fruit ready for harvest.
Colour: Sepia; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cacao--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Theobroma--Trinidad and Tobago